The alternative enzymes-bearing tunicates lack multiple widely distributed genes coding for peripheral OXPHOS subunits - Othonicar, Murilo Ferreira [UNESP]; Garcia, Geovana Siqueira [UNESP]; Oliveira, Marcos Túlio [UNESP] (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)
The respiratory chain alternative enzymes (AEs) NDX and AOX from the tunicate Ciona intestinalis (Ascidiacea) have been xenotopically expressed and characterized in human cells in culture and in the model organisms Drosophila melanogaster and mouse, with the purpose of developing bypass therapies to combat mitochondrial diseases in human patients with defective complexes I and III/IV, respectively. The fact that the genes coding for NDX and AOX have been lost from genomes of evolutionarily successful animal groups, such as vertebrates and insects, led us to investigate if the composition of the respiratory chain of Ciona and other tunicates differs significantly from that of humans and Drosophila, to accommodate the natural presence of AEs. We have failed to identify in tunicate genomes fifteen orthologous genes that code for subunits of the respiratory chain complexes; all of these putatively missing subunits are peripheral to complexes I, III and IV in mammals, and many are important for complex-complex interaction in supercomplexes (SCs), such as NDUFA11, UQCR11 and COX7A. Modeling of all respiratory chain subunit polypeptides of Ciona indicates significant structural divergence that is consistent with the lack of these fifteen clear orthologous subunits. We also provide evidence using Ciona AOX expressed in Drosophila that this AE cannot access the coenzyme Q pool reduced by complex I, but it is readily available to oxidize coenzyme Q molecules reduced by glycerophosphate oxidase, a mitochondrial inner membrane-bound dehydrogenase that is not involved in SCs. Altogether, our results suggest that Ciona AEs might have evolved in a mitochondrial inner membrane environment much different from that of mammals and insects, possibly without SCs; this correlates with the preferential functional interaction between these AEs and non-SC dehydrogenases in heterologous mammalian and insect systems. We discuss the implications of these findings for the applicability of Ciona AEs in human bypass therapies and for our understanding of the evolution of animal respiratory chain.
Os tunicados portadores de enzimas alternativas carecem de múltiplos genes amplamente distribuídos que codificam para subunidades periféricas de OXPHOS
Keywords: Mitochondria; Drosophila melanogaster; Tunicata